Implementação de um sistema de aquisição de dados da técnica de judô Osotogari utilizando dummy na realização do uchikomi - Nagata, Eduardo Yoshinori [UNESP] (2015)
Judo is a worldwide practiced sport which requires physical fitness for better performance. For the fulfilment of the techniques, it is necessary the coordination of lower and inferior limbs, as well as the synchronization of power delivered by the limbs to achieve efficiency on the gesture. The objective of the present study was to develop an equipment for the performance evaluation of the judo technique Osotogari during uchikomi training, through the behavior of strength signals. The device had 4 load cells placed on four locations of the uke’s body (one who receives the technique) on the tori (one who performs the technique) while applying the technique. The device as built based on a dummy, with one load cell placed on the left side of the chest, other on the back side of the right thigh. The dummy was dressed in a adapted kimono, that received a load cell on the right sleeve and another one on the left side collar. 12 subjects of right side dominance took part on the survey, 7 of them were beginners and 5 were experienced. Each of these subjects performed 1 serie of 10 repetitions of Osotogari. A significant difference was observed between experienced subjects and beginners for the sleeve and the collar load cells data. In the other hand, no significant difference was observed on the chest and thigh load cells. Moderate linear correlation was observed between peak force data of the sleeve and collar load cells, which can be explained by the hands’ temporal synchronization and rhythm. It was observed that there is an ideal moment to apply strength when performing the technique, in order to achieve better performance. The dummy is intended to meet the need for more practical performance analysis methods, contributing this way to the advance in athletes training